2022
DOI: 10.1002/joom.1176
|View full text |Cite
|
Sign up to set email alerts
|

Breaking out of the pandemic: How can firms match internal competence with external resources to shape operational resilience?

Abstract: This study explores how firms sought to effectively match their internal competence with external resources from the supply chain network to improve operational resilience (OR) during the COVID‐19 pandemic. Drawing upon matching theory, this study provides an internal–external matching perspective based on flexibility–stability features of OR to explain the operational mechanisms underlying the different matchings between internal flexibility (i.e., product diversity)/stability (i.e., operational efficiency) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 75 publications
3
41
0
Order By: Relevance
“…The speed of recovery requires a high level of adaptability in response to the changing external environment and reconfiguration of internal resources through incremental innovations to internal processes and systems. As Li et al (2022) suggested, digital technologies that are implemented for internal process efficiency create an internal environment conducive to any innovation plans; internal stability and supply chain flexibility are complementary for innovation plans leading to operations resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of recovery requires a high level of adaptability in response to the changing external environment and reconfiguration of internal resources through incremental innovations to internal processes and systems. As Li et al (2022) suggested, digital technologies that are implemented for internal process efficiency create an internal environment conducive to any innovation plans; internal stability and supply chain flexibility are complementary for innovation plans leading to operations resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Operations resilience is a firm’s ability to return to the original state of operations after a disruption and requires operations to be stable and flexible (Essuman et al , 2020; Li et al , 2022). Firms must recover and persist in their operations during and after disruptions, such as rapid and effective restoration of operations is required for firms to remain competitive (Munoz and Dunbar, 2015; Zhao et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…High product diversity together with the central position in the supply chain helped improve the operational resilience of some companies during the COVID-19 pandemic (Li et al, 2022 ). However, the revealed benefits of substitution do not always imply increasing product variety or capacity.…”
Section: Discussionmentioning
confidence: 99%
“…One common objective way to measure resilience is to assess the changes that resilience evokes in other performance outcomes (DesJardine et al, 2019). For example, scholars have used changes in stock price (DesJardine et al, 2019; Sajko et al, 2021), profitability (Dimitriadis, 2021; Lin et al, 2021; Ortiz‐de‐Mandojana & Bansal, 2016), operating avenue (Ge et al, 2022; Li et al, 2022), and inventory (Lin et al, 2021) to measure a firm's resilience in the face of a crisis. An emerging stream of literature has begun to measure resilience from the perspective of production function (Dohale et al, 2022; Dormady et al, 2019), which depicts the efficiency and effectiveness of firms' efforts to configure the combination of inputs to obtain production targets or maximize profits (Rose, 2004).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%